(3JfGRY GdbhGfjf ai eSGFd GdedcnqjI GdacQnqjI (B/ s - (3gGjOi YjSi MSf Ydi MSfs; (3YHOGdefYe ReRes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2018)
(3LGA ehVhY GdQSGdI (B((3JfGRY GdbhGfjf ai eSGFd GdedcjI GdacQjI(B) (3ebnqSkeG Ydi(B: (3aUd JegjOi h KdGKI CHhGH; JfGhd GdHGH GdChd(B: (3JMOjO GdbGfhf GdhGLH GdJWHjb Ydi eSGFd GdedcnqjI GdacQnqjI(B: (3YHQ aUdjf; JfGhd GdaUd GdChd(B: (3bGfhf HdO GdCUd (B((3HdO GdefTC(B): (3HjfeG YGdL GdaUd GdKGfi(B: (3bGfhf HdO WdH GdMeGjI(B. (3Ke LGA GdHGH GdKGfj eHjkfG(B: (3fWGb GdbGfhf hGLH GdJWHjb Ydi eSGFd GdedcjI GdacQjI h ETcGdjGJ JWHjbg(B: (3YHQ KdGKI aUhd; MjK JfGhd GdaUd GdChd(B: (3GdeSGFd GdJi JONd ai GNJUGU bGfhf HdO WdH GdMeGjI(B: (3h nHjf GdaUd GdKGfi(B: (3GdGSJKfGAGJ GdJi JQO Ydi JWHjb bGfhf HdO WdH GdMeGjI(B: (3h GSJhba GdaUd GdKGdK YfO(B: (3ETcGdjGJ JWHjb GdbGfhf hGLH GdJWHjb Ydi Mbhb GdedcjI GdacQjI(B. (3h YGdL GdHGH GdKGdK(B: (3efgL GdbhGYO GdehVhYjI h eSGFd GdedcnqjI GdacQnqjI(B: (3YHQ aUdjf(B: (3JfGhd GdaUd GdChd(B: (3OhQ GdJTQjY GdOGNdj aj hVY GdbhGYO GdehVhYjI GdeJYdbI HMeGjI Mbhb GdedcjI GdacQjI(B: (3h hba GdaUd GdKGfi YfO(B: (3OhQ GdGJaGbjGJ GdOhdjI ai GdTCf PGJgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi , (B2018s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B521-565s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3GdedcnqjI GdacQnqjI s; (3Mbhb GdedcjI GdacQjI s; (3eSGFd GdedcnqjI GdacQnqjI s; (3bGfhf HdO WdH GdMeGjIs; (3eHOC GdeYGedI GdhWfjIs; (3eHOC GdMO GdGOfi ef GdMeGjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs